An Efficient Rechargeable Aluminium–Amine Battery Working Under Quaternization Chemistry - Wang, Gang; Dmitrieva, Evgenia; Kohn, Benjamin; Scheler, Ulrich; Liu, Yannan; Tkachova, Valeriya; Yang, Lin; Fu, Yubin; Ma, Ji; Zhang, Panpan; Wang, Faxing; Ge, Jin; et al. (Angewandte Chemie International Edition, 2022)
Rechargeable aluminium (Al) batteries (RABs) have long-been pursued due to the high sustainability and three-electron-transfer properties of Al metal. However, limited redox chemistry is available for rechargeable Al batteries, which restricts the exploration of cathode materials. Herein, we demonstrate an efficient Al–amine battery based on a quaternization reaction, in which nitrogen (radical) cations (R3N.+ or R4N+) are formed to store the anionic Al complex. The reactive aromatic amine molecules further oligomerize during cycling, inhibiting amine dissolution into the electrolyte. Consequently, the constructed Al–amine battery exhibits a high reversible capacity of 135 mAh g−1 along with a superior cycling life (4000 cycles), fast charge capability and a high energy efficiency of 94.2 %. Moreover, the Al–amine battery shows excellent stability against self-discharge, far beyond conventional Al–graphite batteries. Our findings pave an avenue to advance the chemistry of RABs and thus battery performance.
CRIS-Team Scopus Importer:2023-03-20
Keywords: Al-Ion Batteries; Amine; Anion Storage; Quaternization